Lung Oxidative Stress, DNA Damage, Apoptosis, and Fibrosis in Adenine-Induced Chronic Kidney Disease in Mice - Nemmar, Abderrahim; Karaca, Turan; Beegam, Sumaya; Yuvaraju, Priya; Yasin, Javed; Ali, Badreldin H. (Frontiers in Physiology, 2017)
It is well established that there is a crosstalk between the lung and the kidney, and several studies have reported association between chronic kidney disease (CKD) and pulmonary pathophysiological changes. Experimentally, chronic renal disease can be caused in mice by dietary intake of adenine. Nevertheless, the consequence of such intervention on the lung received only scant attention. Here, we assessed the pulmonary effects of adenine (0.2% w/w in feed for 4 weeks)-induced CKD in mice by assessing various physiological histological and biochemical endpoints. Adenine treatment induced a significant increase in urine output, urea and creatinine concentrations, and it decreased the body weight and creatinine clearance. It also increased proteinuria and the urinary levels of kidney injury molecule-1 and neutrophil gelatinase-associated lipocalin. Compared with control group, the histopathological evaluation of lungs from adenine-treated mice showed polymorphonuclear leukocytes infiltration in alveolar and bronchial walls, injury and fibrosis. Moreover, adenine caused a significant increase in lung lipid peroxidation and reactive oxygen species and decreased the antioxidant catalase. Adenine also induced DNA damage assessed by COMET assay. Similarly, adenine caused apoptosis in the lung characterized by a significant increase of cleaved caspase-3. Moreover, adenine induced a significant increase in the expression of nuclear factor erythroid 2–related factor 2 (Nrf2) in the lung. We conclude that administration of adenine in mice induced CKD is accompanied by lung oxidative stress, DNA damage, apoptosis and Nrf2 expression and fibrosis.